Dose related inhibitor effect of enrofloxacin on in vitro feline spontaneous myometrial contractility - Dogan, Halef; Ocal, Halis; Safak, Tarik; Kilinc, Mehmet Akif; Risvanli, Ali (Elsevier, 2022)
Enrofloxacin is one of the most widely used antibacterial drugs in feline medicine. This study investigated the effects of enrofloxacin on in vitro feline spontaneous myometrial contractility at different sexual stages. Uterine samples of the 20 queen cats at different sexual periods were placed in a tissue bath, and in vitro spontaneous stretch-induced myometrial contractions were recorded for 10 mM. The tissue bath was adjusted for cumulative enrofloxacin concentrations of 0.25 mM, 0.50 mM, 1.00 mM, and 2.00 mM, respectively. Myometrial contractions were recorded for 10 mM after each dose was adjusted in the tissue bath. It was observed that enrofloxacin caused a significant decrease in the peak amplitude and area under curve, while causing an increase the frequency of stretch-induced myometrial contractions in a dose dependent manner in vitro at all sexual stages. The current preliminary study concluded that enrofloxacin has an inhibitory effect on in vitro feline uterine myometrial activity at all sexual stages. It is recommended to take this medical effect into consideration and apply enrofloxacin and uterotonics together in treatment of uterine infections in feline medicine.
Keywords: Enrofloxacin; In vitro; Uterus; Contractility; Queen cat